Committees On Human Resources And Compensations In Russian Non-Public State Companies - Pozdnyakov, Konstantin K. (Opción, 2019)
To ensure the effective work of the Board of Directors in accordance with the best management practices, committees should function more effectively. In many mid-sized state companies, committees under the Board of Directors have mainly a decorative function and fail to provide the expected advantage. Hence, corporate control is decreased. Insufficient control (audit committee) and remuneration policy (HR committee) lead to adverse consequences. Based on own experience and world’s best practices, the author proposes means to improve the incentives in the sphere of corporate governance and the work of top management and Board of Directors in state companies.